1973
DOI: 10.1677/joe.0.0580675
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Concentration of Prolactin and Adrenal Corticosteroids in Rat Plasma During Pregnancy and Lactation

Abstract: In spite of the importance of prolactin and adrenal corticosteroids in the normal control of the mammary gland (Cowie & Tindal, 1971) there has been no report of their simultaneous measurement in rat plasma during pregnancy and lactation. There is no agreement on the pattern of change in corticosteroid concentration at the time of lactogenesis and parturition (Gala & Westphal, 1965;Kuhn, 1969).Primiparous CFE strain rats, allotted randomly to groups on day 0 of pregnancy, were decapitated without prior disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

1974
1974
1989
1989

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 3 publications
4
16
0
1
Order By: Relevance
“…The levels of serum and pituitary prolactin found in these mice were strikingly similar to those reported in the rat (Reece & Turner, 1937;Grosvenor & Turner, 1960;Amenomori, Chen & Meites, 1970;Simpson, Simpson, Sinha & Schmidt, 1973). In general, prolactin levels in serum were low through most of pregnancy, and it was only near term that the concentrations rose to any marked extent.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The levels of serum and pituitary prolactin found in these mice were strikingly similar to those reported in the rat (Reece & Turner, 1937;Grosvenor & Turner, 1960;Amenomori, Chen & Meites, 1970;Simpson, Simpson, Sinha & Schmidt, 1973). In general, prolactin levels in serum were low through most of pregnancy, and it was only near term that the concentrations rose to any marked extent.…”
Section: Discussionsupporting
confidence: 84%
“…Although blood was sampled in our study between 09.00 and 10.00 h, a small peak of serum prolactin on day 5 was nonetheless evident. Such a brief rise in serum prolactin in early gestation was also noted by Amenomori et al (1970), Linkie & Niswender (1972) and Simpson et al (1973). Although we did not detect a simultaneous increase in total mammary DNA or RNA content in our experiments, Traurig (1967) observed a high rate of cell proliferation in the mammary gland at this time.…”
Section: Discussionsupporting
confidence: 71%
“…Removal of the ovaries alone or the adrenal medulla alone did not affect either maternal core temperature or contact time, while removal of the entire adrenal gland (with both medulla and cortex) decreased maternal temperature and increased maternal contact time to the same extent as the double operation . These data suggested that adrenocortical glucocorticoids, which are normally elevated during lactation (Simpson, Simpson, Sinha, & Schmidt, 1973), induce the chronic increase in maternal temperature. This notion was reinforced when demonstrated that replacement therapy with corticosterone and cortisol, but not aldosterone (the dominant adrenal mineralcorticoid) or progesterone (the precursor of both adrenal mineral-and glucocorticoids), restored the normally elevated maternal temperature and normal contact pattern.…”
Section: Control Of the Chronically High Maternal Heat Loadmentioning
confidence: 84%
“…Direct perfusion of distal convoluted tubules indicated the occurrence of a similar phenomenon (Morgan & Berliner, 1969;Wright, 1982). However, the increased plasma concentrations of progesterone (Pepe & Rothchild, 1974;Arthur & Green, 1983) prolactin (Simpson, Simpson, Sinha & Schmidt, 1973;273 S. K. ARTHUR AND R. GREEN Arthur & Green, 1983) and corticosterone (Simpson et al 1973) during lactation might be responsible for the increased distal reabsorption. Neither progesterone nor prolactin concentrations mirror the changes in renal function (Arthur & Green, 1983) but the role of corticosterone is not clear.…”
Section: Discussionmentioning
confidence: 97%